Effect of tool traverse speed on joint line remnant and mechanical properties of friction stir welded 2195-T8 Al–Li alloy joints - Zhang, Qingsong; Yan, An; Chen, Ke; Dong, Fengbo; Jia, Hongde; Wang, Min (High temperature materials and processes, 2023)
AA2195-T8 Al–Li alloy plates were welded by friction stir welding (FSW) at tool rotational speed of 1,000 rpm and tool traverse speeds (TS) of 100–400 mm·min under three types of butting surface conditions, i.e., (1) without butting surface treatment, (2) butting surface milled, and (3) bead-on-plate welding. The effect of welding heat input and butting surface condition on joint line remnant (JLR) and mechanical properties of friction stir welded 2195-T8 Al–Li alloy was investigated comprehensively. In the stir zone of 2195-T8 FSW joints, there exists JLR composed of alumina-particle arrays and microcracks generated from the initial butting surface, and the morphology of JLR would evolve from smooth to serrate as TS increases. Moreover, as TS increases (i.e., the welding heat input decreases), JLR deteriorates the tensile strength of the 2195-T8 FSW joints, with joints prematurely fracturing along JLR. The fracture mode of 2195-T8 FSW joints was considered to be determined by the lower one between strength of JLR ( ) and strength of the lowest hardness zone ( ), and JLR tends to be the fracture path at lower welding heat input. Furthermore, butting surface treatment (milling off oxide layer prior to welding) was found to be able to make the JLR in the 2195-T8 FSW joints less distinct and thus improve , while fracture along JLR could not be avoided.